A lab-customized autonomous humanoid apple harvesting robot. (December 2021) - Yu, Xiaojun; Fan, Zeming; Wang, Xingduo; Wan, Hao; Wang, Pengbo; Zeng, Xilei; Jia, Feng
Abstract: This paper presents an autonomous humanoid robot, namely, LABOR, for apple harvesting. Comprised of a binocular camera, a humanoid dual-arm operating system, and a mobile vehicle platform, the devised robot is capable of identifying, positioning, grasping, and picking up apples via its vision identification and dual-arm harvesting systems. Both the robot structure design and the functional systems, as well as their implementations are described in detail and were verified via experiments in a simulated orchard environment. Results show success rates of 82.5% and 72% for the apple recognition and harvesting functions respectively, and the average apple harvesting time was approximately 14.6 s. The wide flexibility and high scalability in the robotic structure, dual-arm coordinate control, and independent harvest planning may facilitate its application in agriculture for the harvesting of other fruits, such as tomatoes, pomegranates, and pears. Highlights: A dual-arm and binocular vision based autonomous robot is customized for apple harvesting. Both robot mechanical structure and the control system are described in detail. All functions of robot are tested and verified in different cases. Feasibility of autonomous robot harvesting is also verified in simulated orchard environment.